A model for construction sector development in middle-income sub-Saharan African countries - Lopes, Jorge; Banaitienė, Nerija (Technological and Economic Development of Economy, 2024)
Buildings and other constructed facilities form the essential framework of a country’s physical and economic infrastructure. Construction serves as a key capital input to production, driving economic growth and wealth generation. This impact can be particularly transformative in low-to-middle-income countries. Physical infrastructure, including construction, is a powerful engine of economic growth and is closely related to national economic performance. However, not all studies agree with the commonly held belief that construction investment has a positive impact on economic growth, particularly concerning the amount of investment and the relationship between construction investment and economic growth. So far, cross-country studies dealing with the construction sector-economic growth relationship have used indicators of national output and construction that are not strictly comparable between countries. This article reviews the main strands of the literature on the role that the construction sector plays in the national economy and economic development. It also uses novel data drawn from the “capital file” of the PENN World Table (version 10.1) to assess the development pattern of the construction sector in two groups of sub-Saharan African (SSA) countries on the middle-income status of economic development, for the period between 1990 and 2019. The study reveals that construction shares, measured as the proportion of gross fixed capital formation attributable to construction in the gross domestic product, revolve around a norm determined by the level of built assets preceding the reference period. The results of the study could have policy implications for the economic sustainability of the construction industry in SSA.first published online 17 May 2024